PERANCANGAN MEDIA KAMPANYE KONSERVASI PENYU UPT (UNIT PELAKSANA TEKNIS) PARIAMAN DALAM BENTUK FILM DOKUMENTER - RETNI AGMALIA, Drs. Syafwan, M.Si, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Turtle conservation is an activity that aims to maintain and preserve the sustainability of populations of sea turtles and their habitats in a sustainable manner. There is now a turtle conservation in Pariaman is in UPT Pariaman. But there are still many who do not know his whereabouts. It is important to know what kind of turtle conservation turtle and the reason why it is conserved.The documentary is one effective medium for delivering information through documentary films more easily attract the attention of the target audience. The purpose of the design of this documentary is to campaign for the conservation of sea turtles, using Expository approach that conveys information to the presented facts in combination with images.Methodology approach departed from the literature and using 5W +1 H to understand all the information in a problem. So the selection of more effective media campaign and the message understood by the target audience.This film begins with an overview of the scarcity of turtles, then an explanation of the turtle conservation UPT like what, operations management and conservation of the latter effect after conservation. In addition to the documentary, the campaign features a media support such as business cards, stickers, handbook, pins, CD labels, CD covers, wall clocks, key chains and mugs which aims to strengthen the major media.Keyword: media campaigns, turtle conservation, documentary.